Problem Potensial dalam Komunikasi Antara Orang Portugal dan Orang Indonesia (Studi pada Civitas Akademika Universidade do Minho) - Yudha, Reza Pradhitya (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2014)
This study intends to describe how stereotypes, prejudice, and ethnocentrism of Portuguese to Indonesian, as well as its appearance factor. Using qualitative approach to the phenomenological method in order to deepen the meaning of subjectivity. Its validity is tested by triangulation data.Researcher concludes the emergence of stereotypes, prejudice, and ethnocentrism are the result of the news media, personal experience, colleagues, and from textbooks. Stereotype, prejudice, and ethnocentrism could be negative; such as Indonesian are likely terrorism or kind and friendly. Language, mindfulness of cultural pluralism, and empathy become an important factor bridging the success of intercultural communication disorders.